MEASURRING COW FARMS EFFICIENCY BY USING THE QUALITY RESPONSE - Ali, E. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
In despite of the expansion of using the dummy variables as a explanatory variables, but their using as a dependent variables is still limited, and the reason of that may be return to may problems when using dummy variables as a dependent variables. the study aimed to using the quality Response Models to Measuring Efficiency of cows farms by random sample including (19) farm from (Abi gherak district). The study estimating the transcendental logarithmic production function by using stochastic frontier Analysis (SFA) to interpret the relation between the return achieved from the cows farms as a dependent variables and each of labor and capital as an independent variables. the function indicates that increasing in labor by (100%) will increase the value of production by (8%), while increase the Capital by (3%), then the study using this function to obtain the technical Efficiency which was in average (75%) , and this indicate deviation in actual production than optimal production by ( 25%) , and the farms can achieve it by using the economic resource in optimum Farm , the Efficiency has inverse relation with the volume of cows , it was (78%) in small projects , while it was (73%) in medium projects, the study estimate the Quality Response Models of logit , Propit and tobit to descover the Effect of independent variables ( numbers of birth, years of experience, numbers of cows age breeder and the educational level ) upon the Probability of Efficiency. the study found that the number of births and educational level were the most important variables , and the most Effecting in Efficiency of the cows Farms, throw MCFR2 and LR statistical the study found that tobit Model was the best. the study recommended to expansion in using the Quality Response Models as an effective approach which give an idea about the effect of the independent variable in the qualitive dual variable.